Identification of an autotransporter peptidase of Rickettsia rickettsii responsible for maturation of surface exposed autotransporters. - Adam M Nock; Karin Aistleitner; Tina R Clark; Dan Sturdevant; Stacy Ricklefs; Kimmo Virtaneva; Yixiang Zhang; Naila Gulzar; Neelam Redekar; Amitiva Roy; Ted Hackstadt (PLoS Pathogens)
Members of the spotted fever group rickettsia express four large, surface-exposed autotransporters, at least one of which is a known virulence determinant. Autotransporter translocation to the bacterial outer surface, also known as type V secretion, involves formation of a β-barrel autotransporter domain in the periplasm that inserts into the outer membrane to form a pore through which the N-terminal passenger domain is passed and exposed on the outer surface. Two major surface antigens of Rickettsia rickettsii, are known to be surface exposed and the passenger domain cleaved from the autotransporter domain. A highly passaged strain of R. rickettsii, Iowa, fails to cleave these autotransporters and is avirulent. We have identified a putative peptidase, truncated in the Iowa strain, that when reconstituted into Iowa restores appropriate processing of the autotransporters as well as restoring a modest degree of virulence.